Pesona Seni dan Teknologi pada Pertunjukan Fire Dance di Komunitas Flownesia - Rifa Fitriana; Rr. Paramitha Dyah Fitriasari; Wiwik Sushartami (Jurnal Kajian Seni, 2020)
Flownesia is one of the Indonesian flow-art communities that use visual performance with fire props. Based on the existing phenomena, researchers see the existence of special tricks that are used when performing and also various forms of property for enchanting the audience, so this research will explore the aesthetic impact that has emerged on visual fire dance performances and the role of technology in the Flownesia community. This research uses a qualitative method, that is done with participant observation. Alfred Gell's (2006) theory of technology of enchantment was chosen to analyze the forms of visual art and technology performances in flow-art performances. The results of this research flow-art performances in the Flownesia community is a manifestation of art and technology, especially when exploring innovations in their performances. The enchantment that displayed is the result of extraordinary techniques also thr concept of modern and tradition, elaborated on the fire dance props. The movement structure, floor pattern, choreography and tool exploration are important aspect to create interesting visual effects in the Flownesia community performance